The Inner Structure of Lampung Song Lyrics - Hilal, Iqbal; Anantama, Muharsyam Dwi; Gustira, Yinda Dwi (International Journal of Multidisciplinary Sciences, 2025)
The lyrics of a song can be a reflection of society's life because lyrics often contain stories or narratives that are drawn from everyday life. Furthermore, song lyrics can also influence and shape the perceptions and behaviors of society. In this research, the inner structure found in the lyrics of the songs "Lampung Mulang Tiyuh," "Tanoh Lado," and "Pung Kelapo Kupung" is analyzed. The method used is content analysis with a qualitative approach. The data in this study consist of words and phrases from the lyrics of the song "Lampung Mulang Tiyuh," popularized by Bustami Zainudin, as well as "Tanoh Lado" and "Pung Kelapo Kupung," popularized by Andi Achmad. The analysis is conducted by deeply discussing the information written or printed in the lyrics. The results of the study show the presence of inner structures such as themes, emotions, tones, and messages in the lyrics of "Lampung Mulang Tiyuh," "Tanoh Lado," and "Pung Kelapo Kupung."